Evaluation of rheological, textural, and sensory characteristics of optimized vegan rice puddings prepared by various plant-based milks - Karimidastjerd, Atefeh; Gulsunoglu-Konuskan, Zehra; Olum, Emine; Toker, Omer Said (WILEY, 2024)
Nowadays, plant-based milks are being considered as an alternative to dairy milk due to their advantages, such as sustainability, reduced allergenicity, health benefits, and lactose-free nature. Plant-based milks are widely used in the preparation of desserts, cheese-like products, and beverages, among other applications. The aim of the present study was to formulate vegan rice puddings using various commercially available plant-based milks as a sustainable alternative to dairy milk. For this aim, central composition design was applied to optimize the key processing parameters of the Thermomix (R), including temperature (80-90 degrees C), time (6-14 min), and the amount of rice flour (6-10%, w/v), using response surface methodology (RSM). According to the RSM results, the optimum conditions were found to be 90 degrees C for 12.5 min with 6.5% rice flour, as they exhibited minimal phase separation and similar rheological and textural properties to dairy rice pudding. Soya milk pudding had the highest hardness value among the other plant-based milk puddings, and whole fat milk, soya, oat, coconut, and cow's milks showed the best gel unity, according to the cohesiveness results. Phase separation, an important parameter for storage stability, was not observed during 7-day storage at 4 degrees C in all groups, except for pistachio milk rice pudding. Rheological results demonstrated that all vegan pudding samples exhibited a gel-like structure with storage modulus (G ') exceeding loss modulus (G '') values. According to the descriptive sensory evaluation, coconut, oat, and soya milk rice puddings received the highest scores in overall acceptability. Our findings suggest that industrial plant-based rice puddings have great potential as a novel product that meets the dietary needs of the vegan community by offering acceptable flavor and texture.
Keywords: plant-based milks; rice pudding; RSM; vegan; PROTEIN-CONTENT; ACID; FORMULATION; ACCEPTANCE; BEHAVIOR; QUALITY; YIELD; FIBER; Food Science & Technology